Open Skies for Africa : Implementing the Yamoussoukro Decision - Schlumberger, Charles E. (World Bank, 2012)
For the purposes of this book, "open skies" refers to a bilateral or multilateral air service agreement that liberalizes the rules for international aviation markets and minimizes government intervention. It can apply to passenger or cargo services or both, for both scheduled and charter air services. This book evaluates Africa's progress toward liberalizing air services. It specifically examines what the term implementation means in the context of applying the principles of one of the major pan-African multilateral agreements, the Yamoussoukro decision. It also highlights the shortcomings of the 20-year-old effort toward liberalizing air services in Africa by analyzing pending or completed implementation steps both on a pan-Africa level and within various regions. The book focuses on the challenges posed by the poor aviation safety and security standards in most African countries. Finally the sector work measures the impact of certain policy steps of the decision and evaluates the economic significance of air transportation and its full liberalization in Africa. It concludes with policy recommendations that aim at completing implementation to fully liberalize Africa's air services.